2014
DOI: 10.1007/s00420-014-1010-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to heavy metals due to pesticide use by vineyard farmers

Abstract: It can be concluded that in the vineyard region assessed, farmers were more susceptible to heavy metal exposure due to pesticide use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
0
8
0
8
Order By: Relevance
“…An elevated exposure to copper may be mainly consequent to environmental pollution from the manufacture of wire, sheet metal, pipe and other metal products [ 2 ]. In addition, mining, waste dumps, combustion of fossil fuels, wood production and phosphate fertilizers release copper in the environment, thus contributing to the actual exposure in humans [ 2 - 4 ]. To date, mismanaged or high copper levels have been involved in the generation of oxidative stress [ 5 ] which plays an important role in cancer development [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…An elevated exposure to copper may be mainly consequent to environmental pollution from the manufacture of wire, sheet metal, pipe and other metal products [ 2 ]. In addition, mining, waste dumps, combustion of fossil fuels, wood production and phosphate fertilizers release copper in the environment, thus contributing to the actual exposure in humans [ 2 - 4 ]. To date, mismanaged or high copper levels have been involved in the generation of oxidative stress [ 5 ] which plays an important role in cancer development [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A maioria foi de estudos internacionais. 72 EUA, 2014 Coorte 32.345 esposas de aplicadores de agrotóxicos da coorte AHS com ≥35 anos Engel et al 73 EUA, 2017 Coorte 30.594 mulheres agricultoras participantes da coorte da AHS com ≥18 anos Lerro et al 74 EUA 21,28,40,[43][44][45]47,48,54,60,[62][63][64][67][68][69][70] , duração da exposição 16,17,19,[21][22][23]28,29,31,36,40,44,48,55,57,61,64,65,67,74 , frequência de uso/aplicação 16,36,45,60,74 , ocupação 16,30,39,46,47,…”
Section: Resultsunclassified
“…II) Condições subclínicas 20,29,[37][38][39][40][42][43][44][45]48,50,[52][53][54][55]62 : alterações bioquímicas, danos genéticos, estresse oxidativo; III) Sinais e sintomas de intoxicação aguda, queixas de saúde [60][61][62][63][64][65][66][67]69,70 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Previous occupational studies have found increased urinary levels of Mn (Canossa et al, 1993) and ethylenethiourea (ETU) (Runkle et al, 2013), the main metabolite of EBDCs, among farmworkers following mancozeb applications on agricultural fields. Another study found increased blood serum levels of Mn in farmworkers exposed to mancozeb compared to unexposed workers (Rocha et al, 2015). Environmental studies in communities living near agricultural fields have also found that closer residential proximity to agricultural use of EBDC fungicides was associated with increased Mn levels in pregnant women's hair (Mora et al, 2014), prenatal dentin from children's shed teeth (Gunier et al, 2013), and home dust samples (Gunier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%